POTENTIAL BACKWARD SPILLOVER FROM FOREIGN COMPANIES TO MSMEs IN EAST JAVA - Dyah Wulan Sari (East Java Economic Journal, 2017)
The presence of foreign firms in a region can create spillovers to other firms, both within the intra-industries (industries itself) and inter-industries (other industries). Spillover from foreign firms can be in the form of technology transfer, efficiency improvement, managerial knowledge which ultimately is expected to increase productivity for other firms not only in large enterprises but also for micro small and medium enterprises (MSMEs). Hence, this paper aims to identify the potential backward spillover of foreign firms to MSMEs in East Java and the individual results show that the four highest backward spillovers values of foreign industries are industry of components and spare parts of the prime mover motor, industry of agricultural and forestry machinery and services for supporting, maintenance and repair, industry of pump and compressor and industry of measurement tools, manual regulator and testing. All of them are respectively located in Surabaya City, Pasuruan District, Pasuruan District and Mojekerto District. Furthermore, the general results show that the potential backward spillover exists in rubber, rubber goods and plastic goods industries as well as chemicals and goods from chemical material industries. The foreign firms which have highest backward spillovers are located in Pasuruan District, Mojekerto District, Sidoarjo District, Surabaya City and Gresik District. Therefore, the provincial government of East Java should immediately prepare and support both technically and financially to MSMEs in providing raw materials required by foreign firms based on the industrial classification and location results of this study. In addition, the provincial government of East Java can coordinate with the district governments in the areas of those foreign firms for preparing MSMEs in supplying raw materials. JEL Classification: F23, L60